Critical Multiliteration Model Based on Project Based Learning Approach in Developing Basic School of Metacognition Thinking Skills - Ani Hendriyani; Etty Rohayati; Ernalis Ernalis; Yusuf Tri Herlambang (Universitas Sebelas Maret, 2019)
The problem is the low ability of students, and the low orientation of developing students' thinking skills in learning, especially the thinking skills metacognition which is the thinking of the 21st century skills. These factors are one of the main factors that are still oriented towards achieving knowledge in a partial-textual way and not an integrative contextual understanding of the knowledge learned. Therefore, there are efforts that can be used to resolve the problem through effective and up-to-date effective models that are effort-oriented in improving students' metacognitive thinking skills, which is through the application of critical literacy models based on project based learning approaches. The critical multiliteration model is a learning model developed based on awareness and recognition of cultural perspectives and the diversity of learning styles. In addition, the critical multiliteration model is a model that is oriented towards efforts to build students' thinking skills through multicontext, multicultural and multimedia approaches. In this context, critical multiliteration models are specifically developed as a dynamic learning approach, where students actively explore problems in real world, provide challenges, and gain deeper knowledge. This is based on the purpose of developing a model oriented to the development of metacognitive thinking skills.